Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Keputusan Pembelian Konsumen Restoran Mie Gacoan Cabang Karawang - Sijabat, Devy Monica; Martini, Nelly (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research uses descriptive and verification methods with a quantitative approach. The population used in this research was consumers of the Mie Gacoan restaurant in the Karawang branch from January to May so that the total number of consumers on average was 42,387 people and the sample used was 397 respondents with a sampling method using the Slovin formula. This research uses a non-probability sampling technique with purposive sampling technique. data analysis techniques using path analysis using Microsoft Office and SPSS tools. The results of this research show that the correlation between the Service Quality and Product Quality variables is 0.840, so it can be concluded that the correlation level is very strong and in the same direction. There is a partial influence between the variables Service Quality and Product Quality on Consumer Purchasing Decisions and there is also a simultaneous influence between the Service Quality and Product Quality variables on Consumer Purchasing Decisions of 0.651 or 65.1% and other variables not examined are 0.349 or 34.9 %